An efficient synthesis of lactacystin beta-lactone. - Donohoe, T; Sintim, H; Sisangia, L; Harling, J (2004)
A key step in the synthesis of lactacystin β-lactone (3), an inhibitor of the 20 S proteasome, was the ammonia-free reductive aldol reaction of pyrrole 1 to form 2 with complete anti selectivity. This route to 3 takes just 13 steps (14% overall yield) and allows the late-stage stereoselective introduction of a methyl group at C4, which is crucial for the production of analogues. Boc = tert-butoxycarbonyl.